Architectural shop drawing of brick wall layout of AT1/AT2 6F-12F (RFA-437_Rev D) - BUCG-ABC Joint Venture (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.